The Kiso Road : the life and times of Shimazaki Tōson - Naff, William E. (Book collections on Project MUSE., 2011)
William E. Naff, the scholar of Japanese literature widely known for his translations of the writings of Shimazaki Toson (1872-1943), spent the last years of his life writing a full-length biography of Toson. The Kiso Road provides an account of this novelist who, along with Natsume Soseki and Mori Ogai, formed the triumvirate of writers regarded as giants in Meji Japan, all three of whom helped establish the parameters of modern Japanese literature. Professor Naff's biography places Toson in the context of his times and discusses every aspect of his career and personal life, as well as introducing a number of untranslated works.